Corporation’s Liability on Illegal Dumping’s Impact on Climate Change according to the UNFCCC and its Implementation in Indonesia - Patra, Elma Eddy; Aida, Melly; Bing, Jean-Baptiste; Davey, Orima Melati (LPPM Universitas Lampung, 2022)
Corporation illegal dumping’s impact on climate change illustrates that corporate economic crime in the environmental field (waste disposal) has a broad effect yet no significant correlation. If this correlation is adequately studied, it can contribute to enforcing legal accountability and optimizing efforts to reduce climate change. To see this correlation, it is necessary to ask whether a corporation has an economic interest that is fought for in disposing of waste irresponsibly and whether parties whose economic interests are harmed. As one of The United Nations Framework Convention on Climate Change (UNFCCC's) members, Indonesia is a country that predominantly relies on its natural resources, while climate change is very detrimental to nature. This research is normative-juridical research which uses secondary type data. Research shows that The UNFCCC does not explicitly prohibit illegal dumping, but it does specify waste management guidelines that are not hazardous to the environment or public safety. Indonesia has ratified the UNFCCC instrument by through Law No. 6 of 1999. From this ratification, Indonesia's effort to reduce illegal dumping is seen through Environmental Protection and Management Plan, Strategic Environmental Studies, and Government Regulation no. 47 of 2012 concerning Social and Environmental Responsibility of Limited Liability. The economic interest of a corporation that illegally dumps is to avoid spending money because the procedure of adequate waste management is high cost.